PENYULUHAN TENTANG KHASIAT TANAMAN BAU-BAU UNTUK OBAT ANTIDIABETES PADA PUSKESMAS TALUN KENAS - Bunga Rimta Barus; Amirullah Harahap (INSTITUT KESEHATAN DELI HUSADA, 2021)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia associated with abnormal carbohydrate metabolism, fats, and protein caused by decreased insulin secretion or decreased insulin sensitivity, or both and cause chronic microvaskular, and neuropathic complication. Plants are a source of secondary metabolite compounds that are useful as medicine. Many types of plants have activities as traditional medicines, one of which is the odorous plant leaves (chromolaena odorata L.) belonging to the Asteraceae family, traditionally used for wound healing, treating infections, diarrhea, antihypertensive, anti-inflammatory, and diuretic. The odor plant (Chromolaena odorata L.) is reported to contain various compounds in the form of essential oils, flavonoids, alkaloids, phenols, saponins, and tannins.Glibenklamid is a group of sulfonylurea drugs that work to stimulate insulin secretion in the pancreas. Compouds that play a role in reducing blood glucose level in bau-bau leaves is flavonoids, tanin, saponins, alkaloids. This researchaims to evaluate the effect of bau-bau leaves ekstract in reducing the glucose level of wistar strain rats. Test results shown that ethanol bau-bau leaves extract with a dose of 100, 200, 300 mg/kgbb was able to reduce blood glucosse levels in diabetic rats induced by allixan and in the positive control of glibenclamide decreased KGD 105 mg/dL. The conclusion of this reserach was leaves bau-bau extract can reduce blood glucose levels in 300 mg/kgbb is the most effective 77 mg/dL.